Simulation of equal channel angular pressing applied to produce structures with ultrafine-sized grains. (22nd January 2010) - Karpuz, Pinar; Simsir, Caner; Gur, C. Hakan
Severe plastic deformation methods are of great interest in industrial forming applications, as they give rise to significant refinement in microstructures and improvements in mechanical and physical properties. In the 'equal channel angular pressing (ECAP)', which is the most common method for production of ultrafine grained bulk samples, very high plastic strains are introduced into the bulk material without any change in cross section. In this study, the plastic deformation behaviour of the materials subjected to ECAP was analysed by modelling the process with Msc.Marc finite element software. Various numerical experiments were carried out for the die angles of 90°, 120° and 150°, different friction conditions, and different round corners. To simplify the problem, plane strain condition and an isothermal system was assumed. Auto-remeshing was applied when the strains reached to very large values. The numerical results are in good agreement with those of the theoretical studies and data in literature.